2014
DOI: 10.5455/ijmsph.2013.111220131
|View full text |Cite
|
Sign up to set email alerts
|

OCT determined macular thickness in diabetic retinopathy and relation to colour vision deficiency patterns

Abstract: Background: Diabetic retinopathy is the most common cause of blindness in industrialised nations and the incidence of diabetes is expected to rise over the next 10 years. Early treatment of proliferative diabetic retinopathy and diabetic maculopathy improves visual outcome and with effective screening, blindness could be reduced. Patients suffering from diabetes mellitus show alterations in their colour perception. Colour vision testing provides a sensitive, non-invasive method to assess macular damage in diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…No change in colour vision was noted at 6 months follow up. Sadiqulla et al 16 reported a red-green loss pattern prevailing then total colour blindness, Shin et al 17 reported a blue-yellow loss pattern, the same reported by Patzetal 18 andMa´ar et al 19 .…”
Section: Results:-mentioning
confidence: 63%
“…No change in colour vision was noted at 6 months follow up. Sadiqulla et al 16 reported a red-green loss pattern prevailing then total colour blindness, Shin et al 17 reported a blue-yellow loss pattern, the same reported by Patzetal 18 andMa´ar et al 19 .…”
Section: Results:-mentioning
confidence: 63%